Mechanism of elevated proinflammatory cytokines in aqueous humor of patients with primary angle-closure glaucoma - Yong Zhang (Guoji Yanke Zazhi, 2017)
Glaucomais a group of diseases characterized by optic atrophy and visual field defect. In China, primary angle closure glaucoma(PACG)is the most common type of glaucoma. The mechanism of glaucoma has many theories, such as mechanical theory and vascular theory. Recent researches found that inflammation may be involved in the pathogenesis of glaucoma. A variety of proinflammatory cytokines significantly increased in aqueous humor of patients with PACG. In this study, we summarized the methods for the detection of aqueous humor, and analyzed the mechanism of the increasing of proinflammatory cytokines in the aqueous humor of patients with PACG.